PENERAPAN KONSEP CRM DALAM PELAYANAN INFORMASI PASIEN REHABILITASI NARKOBA BERBASIS MOBILE - Andri Perangin-angin; Alfonsus Situmorang; Doli Hasibuan (Universitas Methodist Indonesia, 2019)
Drug rehabilitation in Bukit Doa Tuntung is one place for drug addicts to be rehabilitated and cured. The lack of delivery of health information and the process of healing time for addicts is still manual where family members must come to see and report is still in the form of paper in conveying the patient's health and the time process of the addict. The concept of CRM that is built is the notification of the patient's condition to the patient's family through the admin contact by using chat as well as the submission of complaints or questionnaires about patient services and can also be via sms notification for the family in the rehabilitation of Bukit Doa Tuntung. For this reason it is hoped that mobile technology that will be used in drug rehabilitation patient information services can later help users get health information easily and quickly.